Analysis of the Effectiveness of kerokan (Coining) to Relieve Dizziness and Colds in Parungponteng District - suhaimi, nurnisaa; siddiq, fahmi; amal, alfi (Corespub, 2024)
This research investigates the effectiveness of coining treatment as a traditional method in relieving cold symptoms in Parungponteng Regency, Tasikmalaya Regency. The research population involved people who had used or had experience with kerokan treatment. Ethnography-based research method with observation, interviews and qualitative data analysis. The research results show that colds are a common health problem in this region, and people tend to choose traditional treatments, such as kerokan, as the main solution. Kerokan treatment is considered effective in relieving cold symptoms, and people have a holistic view of health. Traditional medicine is considered cheap, easily accessible, and preserves cultural traditions. This research highlights the importance of understanding society's holistic view of health and the preservation of traditional healing practices in the context of health care.